Management of Venous Thromboembolism in Patients with Hereditary Antithrombin Deficiency and Pregnancy: Case Report and Review of the Literature. (10th January 2017) - Refaei, Mohammad; Xing, Lydia; Lim, Wendy; Crowther, Mark; Boonyawat, Kochawan
Abstract : Background . Hereditary antithrombin deficiency is a thrombogenic disorder associated with a 50–90% lifetime risk of venous thromboembolism (VTE), which is increased during pregnancy and the puerperium in these patients. We present a case of a woman with antithrombin (AT) deficiency who presented with a VTE despite therapeutic low molecular weight heparin (LMWH). Though the pregnancy was deemed unviable, further maternal complications were mitigated through the combined use of therapeutic anticoagulation and plasma-derived antithrombin concentrate infusions to normalize her functional antithrombin levels. Methods . A review of the literature was conducted for studies on prophylaxis and management of VTE in pregnant patients with hereditary AT deficiency. The search involved a number of electronic databases, using combinations of keywords as described in the text. Only English language studies between 1946 and 2015 were included. Conclusion . Antithrombin concentrate is indicated in pregnant women with hereditary AT deficiency who develop VTE despite being on therapeutic dose anticoagulation. Expert opinion suggests AT concentrate should be used concomitantly with therapeutic dose anticoagulation. However, further high-quality studies on the dose and duration of treatment in the postpartum period are required. Use of AT concentrate for prophylaxis is controversial and should be based on individual VTE risk stratification.